Influence of low‐molecular‐weight heparin injection sites on local bruising and pain: A systematic review and meta‐analysis. - Li, Yun; Dong, Shujie; Wang, Panfeng; Sun, Jianjun; Jiang, Hua; Liu, Fang (Journal of Clinical Pharmacy & Therapeutics, 2021)
What is known and objective: Subcutaneous administration of low‐molecular‐weight heparin (LMWH) may cause complications such as haematoma, bruising and pain at different injection sites. Several studies have been carried out to investigate whether bruising and pain depend on injection sites; however, the results have been conflicting, and a clear consistent conclusion has not been reached. The purpose of this systematic review and meta‐analysis was to assess the incidence and severity of bruising and pain after subcutaneous injection of LMWH in different sites. Methods: Two reviewers independently searched the Cochrane Library, PubMed, Embase, China National Knowledge Infrastructure (CNKI) databases for randomized controlled and self‐controlled trials reporting side‐effects from LMWH with different subcutaneous injection sites. Cochrane bias risk assessment tools and the Newcastle–Ottawa Scale (NOS) were used to evaluate the quality of the randomized controlled and self‐controlled trials, respectively. Rev Man 5.3 software was used to analyse the data that were extracted after quality assessment to determine the incidence and severity of side‐effects at different subcutaneous injection sites. Results and discussion: A total of eleven studies were included in this analysis. The meta‐analysis provided evidence that subcutaneous injection in the abdominal area had a lower incidence of bruising than that in the arm area (risk ratios: 0.76; 95% confidence interval: 0.64–0.90; I2 = 52%, p <.05), but the difference in the bruising size between the two injection sites was marginally significant (standardized mean difference: 0.08; 95% confidence interval: −0.45 to 0.62; I2 = 85%, p >.05). There was also no significant difference in the bruising size between subcutaneous injection in the abdominal area and subcutaneous injection in the thigh area (standardized mean difference: −0.16; 95% confidence interval: −0.34 to 0.22; I2 = 32%, p >.05). Subcutaneous injections in the abdominal area had a lower severity of pain than injections in the arm area (risk ratios: 0.57; 95% confidence interval: 0.48–0.67; I2 = 81%; p <.05), but no statistically significant difference was shown between the pain intensity in the abdominal and arm area (mean difference: −1.64; 95% confidence interval: −4.36 to 1.08; I2 = 99%; p >.05). What is new and conclusion: Subcutaneous injection of LMWH in the abdominal area could reduce the incidence of side‐effects at the injection site and reduce patient discomfort. The abdomen is proposed as the first choice of injection site for LMWH. The findings provide useful information to nurses in clinical practice when choosing the subcutaneous injection site for LMWH. The systematic review shows that subcutaneous injection of LMWH in the abdominal area could reduce the incidence of side effects in the injection site and decrease patient discomfort.